Comprehensive Evaluation of the Accelerated Aging Law of NEPE Propellants - Yulong Liang; Mi Zhang; Hui Ren; Qingjie Jiao (Journal of Chemistry)
In order to study the accelerated aging law of nitrate ester plasticized polyether (NEPE) propellants, the mechanical properties, weight loss, adhesive network structure fracture, and stability of NEPE propellants during storage were analyzed. The results show that the maximum tensile strength σm shows good change law with the increase of storage time, and the failure of NEPE propellants is mainly strength failure. The content of the stabilizer decreased with the increase of storage time. With the prolongation of storage time, the weight loss ratio increases gradually with good regularity. The decomposition of the components in the propellant leads to the degradation of the polyethylene glycol (PEG) network structure. The thermal decomposition of the nitrate plasticizer in NEPE propellants will occur, and the products will cause the adhesive network structure to decompose and break the chain, leading to the destruction of the matrix structure. The thermal decomposition of the propellant has temperature-increasing rate dependency.